The Phoenix Biennial. - The Phoenix Biennial, 1983 (Phoenix : Phoenix Art Museum, 1983)
Anderson, David ; App, Timothy ; Taber-Borcherdt, Lynn ; Herritt, Linda ; Johnson, Erick C. ; Langerman, Elaine Marcus ; Levin, Eli ; Loving, Reg ; de Matties, Nick ; Marcus-Orlen, Gail ; Orlinsky, Elaine Kay ; Roberts, Holly ; Widdicombe, Robert A.
The Phoenix Biennial, Phoenix Art Museum, Phoenix, May 13, 1983 - June 19, 1983
boek